The evolutionary diversity of urban forests depends on their land-use history - Borges, Erica Rievrs; Dexter, Kyle G.; Bueno, Marcelo Leandro; Pontara, Vanessa; Carvalho, Fabrício Alvim (Urban ecosystems, 2020)
Urbanization leads to strong modifications of landscape structure and ecosystem functioning, and urban areas are spreading rapidly. The aim of this study was to investigate how phylogenetic diversity and composition of tree species are affected by urbanization itself and land-use history. We found that species richness, rarefied species richness and phylogenetic diversity are all affected by the land-use history of urban forests. Indeed, forests that regenerated from cropland, and particularly those regenerated from denuded landscapes, showed strong phylogenetic clustering, which was also related to their high perimeter-area ratio. Our analyses of phylogenetic composition show that urban forests without land-use history are compositionally indistinguishable from mature, non-urban forests. These two forest types house a diversity of evolutionary lineages and no specific lineage is a strong indicator of these forest types. In contrast, the two urban forest types with anthropogenic land-use history have a few, distinct lineages that are strongly associated with each of them, respectively. Overall, our results suggest that urban forests without previous land-use can house substantial amounts of angiosperm evolutionary diversity, which highlights the importance of preserving natural forest fragments as cities expand. This study highlights the substantial value of tropical urban forests and the importance of considering information on land-use history, even when studying urban environments.